Study of the thermodynamics and conformational changes of collagen molecules upon self-assembly. (May 2021) - Zhu, Shichen; Yu, Xiaoyue; You, Juan; Yin, Tao; Lin, Yuanli; Chen, Wenxin; Dao, Linrui; Du, Hongying; Liu, Ru; Xiong, Shanbai; Hu, Yang
Abstract: The emphasis on mechanism of collagen self-assembly shows great significance for development of collagen-based materials with targeted attributes. Here, combination of isothermal titration calorimetry (ITC) dilution experiments, circular dichroism (CD) and FTIR measurements were employed to investigate the thermodynamic differences and corresponding mechanisms associated with self-assembly of acid-soluble collagen (ASC) and pepsin-soluble collagen (PSC). Firstly, the microrheology measurements of ASC and PSC under the different temperatures (20 °C, 25 °C, 30 °C and 37 °C) had confirmed the temperature induced collagen aggregation. The several thermodynamic parameters (Gibbs free energy change, enthalpy change and entropy change) and the critical mass concentration (CMC) of ASC and PSC, obtained by ITC dilution experiments, decreased with the rising temperatures. The magnitudes of negative Gibbs free energy changes were always higher for ASC than that of PSC, indicating former was more energetically favorable. Besides, the self-assembly of both two collagens were driven by hydrophobic interactions, as evidenced by a negative heat capacity value (ΔCp, mic <0). Specifically, the hydrophobic effects improved due to the transformation of PPII into β-sheet conformations upon collagen self-assembly, as supported by differential CD spectra and FT-IR measurements. Overall, ASC had a higher PPII population than PSC at most temperatures, which may elaborate the thermodynamic differences of two collagens in terms of secondary structure. Graphical abstract: Image 1 Hightlights: Thermodynamics of collagen assembly were studied by isothermal titration calorimetry. Conformation transforms from PPII helix to β-sheet upon collagen self-assembly. Enhancing hydrophobic effects from structure changes accelerate fibrillogenesis.